Maqasid-Based Interpretation of Socio-Legal Qur’anic Verses: A Methodological Analysis of Mahmud Shaltut’s Tafsir - Syafril, Syafril; Efendi, Yusuf; Farina, Dahlia; Musdalifa, Deby Habja; Ritonga, Mahyudin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article examines Mahmud Shaltut’s interpretation of socio-legal Qur’anic verses through a maqasid al-shari‘ah–based approach, focusing on its methodologicalframeworkand implications for contemporary Islamic legal thought. Employing qualitative library research with a descriptive-analytical design, the study analyzes Shaltut’s exegetical works—particularly Tafsiral-Qur’anal-Kari and Al-Islam‘Aqidah waSyari‘ah—usingqualitative content analysis. The findings reveal that Shaltut positions maqasid al-shari‘ah not merely as a complementaryprinciplebut as a central hermeneutical framework guiding socio-legal interpretation. Through a thematic analysis of three key issues—women’s leadership (Q.S. An-Nisa’: 34), interreligious relations and peace (Q.S. Al-Baqarah: 256; Al-Anfal: 61), and economic justice (Q.S. Al-Baqarah: 275–280)—this study demonstrates that Shaltut consistently applies a tripartite model of ijtihad that integrates textual analysis, socio-historical context, and the higher objectives of Islamic law. His interpretive approach prioritizes the spirit of the law (ruh al-tashri‘), substantive justice, and public welfare (maslahah), allowing for contextual legal reconstruction without undermining the authority of the Qur’anic text. This study concludes that Shaltut’s maqasid-based tafsir represents a contextual-progressive exegetical modelthat significantlycontributes to the development of contemporary socio-legal hermeneutics and offers a viable methodological foundation for addressing issues of gender justice, peaceful interreligious coexistence, and equitable economicsystems.